Prevalence of cholelithiasis in patients with chagasic megaesophagus Prevalência de colelitíase em pacientes com megaesôfago chagásico - Eduardo Crema; Ellen Caroline Rosa Resende Silva; Priscila Melo Franciscon; Virmondes Rodrigues Júnior; Aiodair Martins Júnior; Celso Júnior Oliveira Teles; Alex Augusto Silva (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: The prevalence of cholelithiasis in the general population ranges from 9 to 18%. This prevalence is known to be higher in the presence of parasympathetic nerve damage of the biliary tract either due to surgery (vagotomy) or neuronal destruction (Chagas disease). The objective of this study was to evaluate the association of cholelithiasis and chagasic or idiopathic megaesophagus. METHODS: The ultrasound scans of 152 patients with megaesophagus submitted to cardiomyotomy and subtotal esophagectomy surgery were evaluated. The presence of cholelithiasis was compared between chagasic and idiopathic esophagopathy and ultrasound and clinical findings were correlated with age, sex and race. RESULTS: A total of 152 cases of megaesophagus, including 137 with chagasic megaesophagus and 15 with idiopathic megaesophagus, were analyzed. The mean age was 56.7 years (45-67) in the 137 patients with chagasic megaesophagus and 35.6 years (27-44) in the 15 cases of idiopathic megaesophagus, with a significant difference between the two groups (p < 0.0001). The group with chagasic megaesophagus consisted of 59 (43%) women and 78 (56.9%) men, while the group with idiopathic megaesophagus consisted of 8 (53.3%) women and 7 (46.6%) men, showing no significant difference between the groups. Of the 137 patients with confirmed chagasic megaesophagus, 39 (28.4%) presented cholelithiasis versus one case (6.6%) in the 15 patients with idiopathic megaesophagus. CONCLUSIONS: The prevalence of cholelithiasis is high in patients with chagasic megaesophagus and preoperative ultrasound should be performed routinely in these patients in order to treat both conditions during the same surgical procedure. INTRODUÇÃO: A prevalência de colelitíase observada na população em geral varia de 9 a 18%. Sabe-se que a prevalência de colelitíase é elevada quando existe lesão nervosa parassimpática das vias biliares, causada tanto por procedimentos cirúrgicos (vagotomias),quanto por destruição neuronal, como observado na forma digestiva da doença de Chagas. Propusemo-nos verificar a associação entre megaesôfago de etiologia chagásica e a presença de colelitíase. MÉTODOS: Avaliou-se prospectivamente o exame ultrassonográfico de 152 pacientes portadores de megaesôfago submetidos à cirurgia de cardiomiotomia e esofagectomia subtotal. Analisou-se comparativamente a esofagopatia chagásica e a idiopática com a presença de colelitíase, correlacionando os dados ultrassonográficos com os achados clínicos, idade, sexo e raça. RESULTADOS: Foram analisados 152 casos de megaesôfago, sendo 137 de etiologia chagásica e 15 idiopáticos. Entre os chagásicos, a idade média foi de 56,7 anos (45-67); e nos idiopáticos, a média de idade foi de 35,6 anos (27-44), verificando-se diferença significativa (p < 0,0001) em relação à média de idade. Dos 137 chagásicos, 78 (56,9%) eram do sexo masculino; entre os 15 idiopáticos, 7 (46,6%) eram do sexo masculino. A comparação entre os grupos em relação ao gênero não mostrou diferença significativa. Dentre os 137 chagásicos detectou-se 39 (28,4%) casos de colelitíase e, dentre os 15 casos de megaesôfago idiopático, constatou-se colelitíase em apenas um (6,6%). CONCLUSÕES: Conclui-se que portadores de megaesôfago chagásico possuem alta prevalência de colelitíase, e que a ultrassonografia deve ser realizada rotineiramente no pré-operatório, a fim de tratar ambas as afecções no mesmo ato cirúrgico.